Electrophysiology and colour: a comparison of methods to evaluate inner retinal function - Kurtenbach, A; Kernstock, C; Zrenner, E; Langrová, H (Documenta ophthalmologica. Advances in ophthalmology, 2015)
PURPOSE: Several methods are routinely used in the clinic to diagnose and monitor diseases of inner retinal function. In this study, we compare four such methods in patients with diabetes and glaucoma, to determine correlations between their results and to determine which method is most sensitive for detecting disease. METHODS: Twenty control subjects, 12 patients with early glaucoma and eight patients with diabetes mellitus, were enrolled in the study. All underwent four examinations: transient pattern electroretinogram (PERG), multifocal pattern electroretinogram (mfPERG), chromatic contrast threshold measurements (protan and tritan), and blue-on-yellow short-wavelength automated perimetry (SWAP). RESULTS: For the total cohort of 40 subjects, the results show a significant correlation between the amplitudes of the PERG and those of the mfPERG, as well as between the tritan contrast thresholds and the SWAP MD. Furthermore, ROC analyses reveal that colour contrast thresholds could significantly distinguish between the patient and the control group. Glaucoma patients alone could also be distinguished. CONCLUSIONS: We conclude that the methods compared in this study show correlations between their results if they are testing same pathway or underling cells, and that the colour contrast threshold is the most sensitive method to detect early functional deficits in diabetic and glaucoma patients.
Keywords: ROC Curve; glaukom; Humans; zraková pole; diabetická retinopatie; Electrophysiology; lidé středního věku; Electrophysiological Phenomena; elektroretinografie; citlivost na kontrast; Female; Aged; mladý dospělý; dospělí; senzorické prahy; Glaucoma; senioři; elektrofyziologie; lidé; Psychophysics; Visual Field Tests; elektrofyziologické jevy; Retinal Cone Photoreceptor Cells; Diabetes Mellitus, Type 1; Diabetes; Retina; diabetes mellitus 1. typu; Adult; Sensory Thresholds; ženské pohlaví; testy zrakového pole; Male; Electroretinography; Middle Aged; Diagnostic tests; Diabetic Retinopathy; Contrast Sensitivity; Young Adult; Color Vision Defects; Visual Fields; ROC křivka; mužské pohlaví; čípky retiny; poruchy barevného vidění